A UX analysis study into ‘bigbluebutton’ with Yıldız Technical Unıversity School Of Foreign Languages users amid COVID-19 precautions - Yalkut-Tezel, Damla (My University, 2020)
Within the scope of the measures taken against the COVID-19 virus, which has shown its effect rapidly worldwide, the schools had to close immediately and after a short time, it was decided to resume education through distance education. In accordance with these decisions, Yıldız Technical University decided to resume the education simultaneously throughout the school, via the BigBlueButton web conferencing system. The aim of this study was to carry out a user experience (UX) study on BigBlueButton system with the instructors and students of Yıldız Technical University School of Foreign Languages, who had become new users of the system in this period and thus analyzed the good and bad aspects of it. The general approach of different generations to the use of technologies in education has a very important effect on user experience analysis of the system; therefore, to be able to better understand the attitude of the instructors and the students, a study on generation cohorts through questionnaires was conducted. The whole study was carried out in three stages: the first and the third stages were carried out through a questionaire study with the participation of 302 students and 25 lecturers from YTU SLF. The first stage questionnaire was a study on the demographic characteristics of the participants; the third stage was a post-use study to examine their experience and emotions towards the system. In the second stage of the research, in the light of the ‘personas’ created in accordance with the usability test principles, a controlled remote user experience was carried out with a focus group of selected 7 participants through AnyDesk software and the BBB demo system. While the findings showed that the attitudes of the participants about the use of technology in education were positive, data obtained showed that they had negative attitudes towards the distance education system and distance education concept. The usability test and post-use survey data showed that the system has problems in areas such as error prevention and recovery, feedback delivery, undo option, and the use of clear icons, and they negatively affect the user experience.

Dünya çapında hızla etkisini gösteren COVID-19 virüsüne karşı alınan önlemler kapsamında okulların eğitime ara vermiş ve kısa bir süre sonra, sosyal mesafe kuralları gereği eğitimi uzaktan eğitim yolu ile devam ettirme kararı alınmıştır. Bu kararlar uyarınca Yıldız Teknik Üniversitesi’nde BigBlueButton web konferans sistemi üzerinden eğitim süreci tüm okulda aynı anda başlatılmıştır. Çalışmanın amacı, bu süreçte sistemin yeni kullanıcıları haline gelmiş olan Yıldız Teknik Üniversitesi Yabancı Diller Yüksekokulu öğretim görevlileri ve öğrencileri ile BigBlueButton sistemi üzerine bir kullanıcı deneyimi (UX) çalışması yürütmek ve sistemin kullanıcılar gözünden iyi ve kötü yönlerini analiz etmektir. Bu çalışma esnasında farklı nesillerin bir arada bulunduğu ve eğitimde teknoloji kullanımında kullanıcı deneyimine nesillerin yaklaşımının da çok önemli bir etkisinin olduğu da göz önünde bulundurularak kuşak kavramları ve katılımcıların kuşak özellikleri incelemesi de yapılmıştır. Çalışma üç aşamada yürütülmüş olup birinci ve üçüncü aşamasında okula mensup 302 öğrenci ve 25 öğretim görevlisinin katılımıyla anket çalışması ile gerçekleştirilmiştir. İlk aşama anketi katılımcıların demografik özellikleri üzerineydi. Araştırmanın ikinci aşamasında kullanabilirlik testi ilkeleri gereğince oluşturulan personalar ışığında AnyDesk programı ve BBB demo sistemi üzerinden odak grup olan 7 katılımcı ile kontrollü uzaktan kullanıcı deneyimi gerçekleştirilmiştir. Üçüncü aşamada uygulanan anket ise sistemi kullandıktan sonra sisteme yönelik duygu ve tutumlarını irdeleyen bir çalışma olmuştur. Bulgular katılımcıların eğitimde teknoloji kullanımı konusunda tutumlarının olumlu olduğunu gösterirken uzaktan eğitim sistemine ve uzaktan eğitim kavramına karşı olumsuz tutumları olduğu verisi elde edilmiştir. Kullanabilirlik testi ve kullanım sonrası anketi verileri sistemin hata bilgilendirme, düzeltme, geri bildirim, geri almaya izin verme, anlaşılır ikon kullanımı gibi alanlarda sıkıntılarının olduğunu ve bunların kullanıcı deneyimini olumsuz yönde etkilediğini göstermiştir.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2020
Keywords: BigBlueButton; Kullanıcı deneyimi; Kullanabilirlik; Kuşak; User experience; UX; Usability testing; Generation cohorts